PV Energy Monitoring and Optimization System with IoT - Budi Artono; Raden Jasa Kusumo Haryo; Kunto Aji Yudhoyono (International Journal of Integrative Research, 2023)
The efficiency of converting sunlight energy into electrical energy which was previously felt to be less effective to be more effective, it is one of the objectives of this study in addition to problems regarding the direction of solar panel trackers which sometimes do not effectively point to the sun so that the energy obtained is less than optimal, then a two-way communication system is made so that it can control and monitor trackers via the internet or what we often know as the Internet of Things (IoT) system. For the research method that researchers use is the research and development method, as a link between the tool and the monitoring system here firebase is used as a database, so that all parameter values in the tool are sent to the database which is then processed and will be displayed on the monitoring website, besides that for control works the other way around, from the website will send a signal to the firebase database which is then forwarded to the tool, we think this is very helpful and simplifies both monitoring and controlling tools in the form of solar panel trackers.